The objectives of Shariah (Maqasid al-Shariah) in nomination for the payment of family takaful benefits - Salleh, Safinar; Halim, Akmal Hidayah; Abdullah, Mohamad Asmadi; Ibrahim, Uzaimah (2018)
A family takaful certificate is normally subscribed by a takaful participant for the purpose of preparing financial support for his dependants after his death. In 2003, the Shariah Advisory Council (SAC) of Bank Negara Malaysia (BNM) resolved that the benefits could be made as a conditional hibah to a nominee named as the beneficiary in the takaful certificate. This resolution has later been codified in the Islamic Financial Services Act (IFSA) 2013. The new law does not specify the individual to be nominated as the beneficiary and the participant is thus free to decide to who the benefits are to be given. In spite of the approval by the SAC, the position of such nomination has stirred debates since the position of the benefit is merely based on the nomination made by the participant. Such benefit would be an estate if the nominee is named as a wasi or executor. However, if the participant opted to name the nominee as a beneficiary under conditional hibah, the benefit would not then be considered as an estate and would absolutely belong to the nominee despite the existence of other dependants who might also be in need of the money. Therefore, this research aims to juristically evaluate the rules on nomination as provided under IFSA 2013 and the status of conditional hibah from the Shariah perspective. This research specifically focuses on family takaful certificates effected by takaful participants upon their lives providing for the payment of takaful benefits upon their death. The research predicates that the application of conditional hibah to the whole of the takaful benefit does not reflect the objectives of Shariah as determination on the status of the benefit is solely based on the nomination made by the participant. Hence, further research should be carried out to ascertain the position of the takaful benefit so that the rights of all parties are protected and not adversely affected.